Evaluation of the histopathologic status of rectal adenocarcinoma and its regional lymph nodes after neoadjuvant therapy, and its relation to the duration of disease-free survival - Farnaz Karimi; Hedieh Moradi Tabriz; Hadi Ahmadi Amoli; Elham Nazar; Amir Abbas Vaezi (Wolters Kluwer Medknow Publications, 2022)
Introduction: Colorectal cancer is one of the most common malignant tumors and has a relatively poor prognosis. Lymph node involvement is considered the most important prognostic factor. Materials and Methods: During a retrospective cohort study, 132 patients with locally advanced rectal cancer who underwent neoadjuvant chemoradiotherapy followed by surgery for resectable rectal cancer from 2010 to 2015 in Sina hospital were reviewed. Results: Multivariable analysis was performed and shown the clinical stage was not a representative factor for disease-free survival (P = 0.187), but Dworak Tumor Regression Grading were significantly associated with higher disease-free survival (P = 0.000) in stage II and stage III. The total number of retrieved lymph nodes and involved lymph nodes in the same clinical stage were statistically associated with higher mean disease-free survival in patients (P = 0.000 in both conditions). Conclusion: In the same clinical stage, increasing the Dworak Tumor Regression Grading reduced the risk of rectal cancer recurrence. Increasing total number of retrieved lymph nodes and involved lymph nodes, 2.14 times and 3.87 times increased the risk of recurrence, respectively.